(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
Correction: On 29th April 2015 the page numbers of this article were changed from 167-173 to 169-175 An investigation was conducted to determine the comparative growth study of supermale tilapia and monosex tilapia in earthen mini ponds from May-July 2012. Four treatments were considered having two replicates. For supermale tilapia treatments were named as ST1 and ST2 and for monosex tilapia were MT1 and MT2. All the fish were of same age group having mean body weight of 1.4 g. Feeding frequency in all the treatments were two times a day. Fish were fed diet at a rate of 30% of their body weight for the first thirty days that was gradually reduced to 15% for the next thirty days and 5% till the termination of the experiment. Final weight, weight gain, average daily weight gain, % weight gain and production of supermale tilapia were significantly (p<0.05) higher than those of monosex tilapia. But SGR (% day), FCR and survival rate of supermale tilapia were not significantly (p>0.05) varied. However, the result of the present study showed that the best weight gain of 124.85 g was observed in ST1 after 90 days culture period. Average weight gain (g) were 1.39, 1.16, 1.14 and 1.05, SGR (per day) were 2.17, 2.09, 2.08 and 2.04%, FCR were 2.98, 2.65, 2.84 and 2.57, survival rate were 96, 94.50, 95 and 91% and fish production were 5053.92, 8926.10, 4108.07 and 7821.41 kg/ha in ST1, ST2, MT1 and MT2 respectively. The present research findings suggested that supermale tilapia has significantly high growth potential compare to monosex tilapia under mini ponds culture condition. Res. Agric., Livest. Fish.2(1): 169-175, April 2015